Pecularities of the representation of concept «childhood» in the novel «a prayer for Owen meany» by John Irving (Eurasian Journal of Philology Science and Education, 2019)
The article investigates the specifics of the implementation of Concept «Childhood» in the novel «APrayer for Owen Meany» by J. Irving. The components of the concept and its main features (young man,temporal characteristics, condition) are analyzed. It is indicated that Childhood is the central theme ofthe novel. It is revealed through the fate of the main character, his aesthetic views, ideals and values.Much attention is paid to the linguistic means used by the writer in the process of characterizing themain character and the events taking place in his life. The article states that the Concept of Childhoodis realized in the work through literary devices such as metaphor, comparison, epithet, synecdoche andparaphrase. They reveal the inner world of the main character, his attitude to the surrounding reality.The article with specific examples substantiates that in the J. Irving’s novel the Concept of Childhoodrealizes in four aspects.